Corporate social responsibility through stakeholder engagement and entrepreneurial communication processes. (2018) - Mella, Piero; Gazzola, Patrizia
The present work, after having built a model for understanding how multinational corporations act and behave both at the national and international level in the fields of corporate social responsibility and sustainable development, will then present how large multinational enterprises react to the increasing pressures from stakeholders to report their corporate social responsibility at the global level. This paper will then draw conclusions about how enterprises integrate ethical values and stakeholder engagement in the strategy. The article is divided into two sections: the first entails a critical review of the literature on shareholder and stakeholder management, corporate social responsibility and stakeholder engagement; the second presents a critical analysis of the corporate social responsibility reporting of five big multinational competitors in the challenging business of adhesive tapes.